Impact of TB on the survival of people living with HIV infection in England, Wales and Northern Ireland. Issue 6 (24th March 2015) - Zenner, Dominik; Abubakar, Ibrahim; Conti, Stefano; Gupta, Rishi K; Yin, Zheng; Kall, Meaghan; Kruijshaar, Michelle; Rice, Brian; Thomas, H Lucy; Pozniak, Anton; Lipman, Marc; Delpech, Valerie
Abstract : Introduction: The impact of TB disease on survival in people living with HIV in high resource settings is not well documented in the antiretroviral treatment (ART) era. We calculated TB incidence rates and compared the mortality of persons with and without HIV-TB in a UK HIV cohort in the post-ART era, to determine the impact of HIV-TB on survival in the UK. Methods: We linked the national cohort of persons (aged ≥15 years) diagnosed with HIV between 2000 and 2008 in England, Wales and Northern Ireland with the national TB register and deaths from the Office of National Statistics. We compared all-cause and AIDS-specific mortality in patients with and without TB by estimating HRs using Cox regression modelling allowing for potential predictors. Results: Overall, 3188 (7.2%) individuals developed TB infection among a cohort of 44 050 HIV-diagnosed persons and 149 663 person-years. The cumulative TB incidence rate was 2.13 per 100 person-years with a spike within the first 6 months after HIV diagnosis. TB coinfected patients comprised 18% of the 1880 deaths during follow-up and 79% of deaths (n=967) in the year following HIV diagnosis. TB coinfection (HR 4.77, 95% CI 4.11 to 5.54) was significantly associated with increased all-cause mortality. Analysis of AIDS-related survival showed similar results. Discussion: The unexpected high mortality in patients with HIV-TB in a population with good healthcare access and ART availability highlights the importance of improving active and latent TB case-finding among patients with HIV, and HIV-testing among patients with TB, to ensure appropriate and prompt treatment initiation for both diseases.